FRUIT CLASSIFICATION BASED ON CONVOLUTIONAL NEURAL NETWORK - et al., P.Ramakrishnan (International Journal of Control and Automation, 2019)
Selecting Fruits with complicated patterns and colors’ may be a difficult task for visually impaired folks. Automatic Fruit recognition is additionally a difficult analysis drawback thanks to rotation, scaling, illumination, and particularly giant intra category pattern variations. we’ve got developed a paradigm system that acknowledges whether or not the given fruit is healthy or non-healthy. If it had been healthy, then it’ll be classified into totally different classes of fruits. we tend to square measure giving the important time fruit pictures that square measure captured exploitation camera. This paper proposes a theme to extract color, form and texture based mostly properties from the given fruit input pictures exploitation HOG, LBP and form based mostly Region Properties activity formula. The healthy and non-healthy fruits square measure recognized. When recognizing the options as healthy, it will be any classified by class wise exploitation Multi-SVM formula. The calorie price of the fruit that was recognized conjointly displayed. This technique achieves high recognition accuracy that considerably the output forms the progressive texture analysis strategies on fruit recognition.